2023
DOI: 10.1177/21582440231173664
|View full text |Cite
|
Sign up to set email alerts
|

Socially and Educationally Distanced: Examining the Views of University Students

Abstract: Although for many students’ stress is a natural part of university life, new stress sources have come into the picture with the pandemic. A “phenomenological” method, one of the qualitative analysis methods, was used in this study, which seeks to reveal the effects of various aspects of the pandemic on the life of university students. The findings show that students want to return to face-to-face education in terms of educational life and, in parallel, find distance education inefficient, have difficulty in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Rapid social, technological and cultural changes have also brought dramatic changes in education. Changing educational paradigms have required revising students’ attitudes towards learning, which determine learning abilities and willingness ( Güngör, 2023 ). There is studies have shown that university students’ attitudes predict their success orientations ( Entwistle, 2012 ; Güngör, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid social, technological and cultural changes have also brought dramatic changes in education. Changing educational paradigms have required revising students’ attitudes towards learning, which determine learning abilities and willingness ( Güngör, 2023 ). There is studies have shown that university students’ attitudes predict their success orientations ( Entwistle, 2012 ; Güngör, 2021 ).…”
Section: Discussionmentioning
confidence: 99%